2009
DOI: 10.2478/10004-1254-60-2009-1927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ethanol and Acetaldehyde Toxicity in Rat Astrocytes in Primary Culture

Abstract: This study compared the effects of toxicity of ethanol and its fi rst metabolite acetaldehyde in rat astrocytes through cell viability and cell proliferation. The cells were treated with different concentrations of ethanol in the presence or absence of a catalase inhibitor 2-amino-1,2,4 triazole (AMT) or with different concentrations of acetaldehyde. Cell viability was assessed using the trypan blue test. Cell proliferation was assessed after 24 hours and after seven days of exposure to either ethanol or aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…Further, unlike ethanol, acetaldehyde does not readily enter the brain; the amount of acetaldehyde formed from ethanol entering the brain and the effects of acetaldehyde in brain are topics of some controversy [30]. We did not block conversion of ethanol to acetaldehyde in our study, so cannot compare toxicities, but acetaldehyde is likely to be 10-20 times more toxic to OL than ethanol, as found for astroglia [29].…”
Section: Individual Th1 Cytokines Protect Ol From Ethanol Toxicitymentioning
confidence: 63%
See 1 more Smart Citation
“…Further, unlike ethanol, acetaldehyde does not readily enter the brain; the amount of acetaldehyde formed from ethanol entering the brain and the effects of acetaldehyde in brain are topics of some controversy [30]. We did not block conversion of ethanol to acetaldehyde in our study, so cannot compare toxicities, but acetaldehyde is likely to be 10-20 times more toxic to OL than ethanol, as found for astroglia [29].…”
Section: Individual Th1 Cytokines Protect Ol From Ethanol Toxicitymentioning
confidence: 63%
“…One study systematically analyzed the sensitivity of astroglia to ethanol and its more toxic metabolite acetaldehyde [29]. At 600 mM ethanol, no astroglial death occurred at 1 day, while at 7 days, 600 and 200 mM ethanol caused 80 and 30% astroglial death, respectively [29].…”
Section: Individual Th1 Cytokines Protect Ol From Ethanol Toxicitymentioning
confidence: 99%
“…This was reported for both the acute and chronic low-dose exposure to ethanol (47,48). Šarc et al's study (49) showed that low-level of exposure to ethanol may result in increased cellular protein content. Therefore, considering the fact that nail salons provide an environment in which low-level exposure to VOC can be assumed, and the fact that ethanol -the most abundant VOC -was found to correlate positively with biomarkers of oxidative stress (the activities of GPx1 and GPx3, GPx1/SOD1 ratio) and DNA strand breakage, a hypothesis might be drawn that low-level exposure to airborne ethanol might be the key (but not the only) factor responsible for induction of mild oxidative stress among nail technicians, the effects of which (such as DNA damage) might have been, however, successfully compensated for by increased activity of cellular antioxidant enzyme system (indicated by increased activities of antioxidant enzymes).…”
Section: Grešner Et Almentioning
confidence: 76%
“…For example, cortical neuron viability is not decreased by EtOH concentrations of at least 100 mM and ACD of at least 1 mM (Lamarche et al., ). In astrocytes, the other major brain glial cells, ACD is 10 to 20 times more toxic than EtOH (Šarc and Lipnik‐Štangelj, ). These authors found that astrocyte viability did not significantly decrease until concentrations above 700 and 50 mM for EtOH and ACD, respectively.…”
Section: Discussionmentioning
confidence: 99%